Люминесцентное определение офлоксацина и ломефлоксацина в сточных водах фармацевтических предприятий - Бельтюкова, С.В.; Ливенцова, Е.О.; Beltykova, S.V.; Liventsova, H.O. (Волин. нац. ун-т ім. Лесі Українки, 2008)
Изучена возможность хроматографического разделения антибиотиков фторхинолонового ряда офлокса- цина и ломефлоксацина с использованием метода тонкослойной хроматографии. Разработана методика определения офлоксацина по сенсибилизированной люминесценции иона Tb (III) и ломефлоксацина по сенсибилизированной люминесценции иона Eu (III) в фазе сорбента в сточных водах фармацевтических предприятий. Possibility of chromatographic division of fluoroquinolone antibiotics – ofloxacin and lomefloxacin was developed. By a thin layes chromatography method the technigue of determination of ofloxacin using the sensitized luminescence of Tb (III) ions and lomefloxacin using the sensitized luminescence of Eu (III) ions in a phase of a sorbent in sewage of the pharmacentical enterptises is developed.
Luminescence Determination of Ofloxacin and Lomefloxacin in Sewage of the Pharmacentical Enterptises
Keywords: люминесценция; европий (III); тербий (III); офлоксацин; ломефлоксацин; сточные воды; luminescence; europium (III); terbium (III); ofloxacin; lomefloxacin; sewage